Rapid and sensitive detection of the vanA resistance gene from clinical Enterococcus faecium and Enterococcus faecalis isolates by loop-mediated isothermal amplification. (March 2019) - Huang, Qian-Qian; Liu, Bin-Bin; Zhu, Hui-Fen; Ma, Jian-Jia; Tsoi, Madeleine; Yao, Bing-Qing; Yao, Li-Chen; Wu, Qiang; Mu, Xiao-Qin; Liu, Shu-Lin
Highlights: Vancomycin-resistant Enterococcus mediated mainly by vanA is a serious problem worldwide. A rapid and sensitive LAMP assay to detect the vanA gene was developed. The assay may have great application potential in clinical diagnosis and epidemiological studies. Abstract: Objectives: Vancomycin resistance in Enterococcus spp., mediated mainly by the vanA resistance gene, has become a major health concern as it has spread worldwide. Therefore, a rapid method is urgently required to detect the vanA gene for timely and appropriate antimicrobial control of resistant Enterococcus infections. Methods: The loop-mediated isothermal amplification (LAMP) assay was optimised for vanA detection in Enterococcus spp. isolates. Results: The LAMP primer set designed in this study could reliably recognise seven distinct regions of the vanA gene and amplify the gene within 25 min at an isothermal temperature of 65 °C with high specificity. The sensitivity of the optimised assay was high, with a detection limit for vanA as low as 100 pg/μL, which is 100-fold more sensitive than the PCR assay. A special advantage of this optimised LAMP method is that the vanA gene could be detected directly from clinical specimens. Conclusion: This optimised LAMP assay has great application potential for efficient detection of vanA in clinical diagnosis and epidemiological studies.